Principles of marketing - Young, Felina C.; Pagoso, Cristobal M. (Manila, Philippines : Rex Book Store, 2008)
The book consists of 16 chapters, it is a simple yet substance laden manuscript for knowing what it means to have a product, to price this product appropriately, to distribute it in different channels of distribution, to promote it effectively and use sales people for maximum productivity.
The marketing function -- The marketing organization -- The marketing environment -- Consumer buying behavior -- Marketing segmentation and product positioning -- Marketing mix: product -- New product development and product life cycle -- Marketing mix: pricing -- Marketing mix: place -- Retailing and wholesaling -- Marketing mix: promotion -- Advertising -- Marketing mix: people -- Marketing research -- Market forecasting -- Strategic marketing plan.
Includes bibliographical references and index.
Keywords: MARKETING